Genetic Correlates of Maladaptive Beliefs: COMT VAL158MET and Irrational Cognitions Linked Depending on Distress. Issue 6 (November 2015) - Podina, Ioana; Popp, Radu; Pop, Ioan; David, Daniel
Abstract: Maladaptive/irrational beliefs are significant cognitive vulnerability mechanisms in psychopathology. They are more likely to be associated with a genetic vulnerability marker under conditions of emotional distress when irrational beliefs are more salient. Therefore, in the current study we investigated the COMT Val 158 Met gene variation in relation to irrational beliefs, assuming this relationship depended on the level of emotional distress. Two hundred and sixty-seven genotyped volunteers were assessed for core/general maladaptive beliefs, as well as trait emotional distress. We focused on context-independent measures of irrational beliefs and emotional distress in the absence of a stressor. As expected, the relationship between COMT Val 158 Met and irrational beliefs depended on the level of emotional distress ( f 2  = .314). The COMT Val 158 Met–irrationality association was significant only when individuals fell in the average to above average range of emotional distress. Furthermore, within this range the Met allele seemed to relate to higher irrational beliefs. These results were significant for overall irrational beliefs and its subtypes, but not for rational beliefs, the functional counterpart of irrationality. In light of the study's limitations, the results should be considered as preliminary. If replicable, these findings have potential implications for therapygenetics, changing the view that COMT Val 158 Met might be of greater relevance when treatment modality does not rely on cognitive variables. Highlights: The COMT Val 158 Met-irrational beliefs link depended on the level of emotional distress. Results contribute to assumptions about biological predispositions to irrationality. The findings have potential implications for the therapygenetics field.